Surgical management of pelvic ring injuries: a study of twelve cases - Nahar, Kuldeep; Nahar, Nikita (International Journal of Research in Orthopaedics, 2020)
The bony pelvic ring is constituted of the sacrum and bilateral innominate bones and stabilized by the sacroiliac, sacrospinous and sacro tuberous ligaments. Secondary stabilization is provided by the iliolumbar ligaments. Injury to the posterior ring structures brings more severe clinical instabilities. Assessment of mechanisms and mode of injuries is necessary for management of pelvic injury. Twelve patients were involved in this study of different kinds of injuries by classification and methods of treatment four patients were treated by anterior fixation. Three by posterior and three by anterior as well as posterior. One was by conservative means. Anterior includes symphysis plating, posterior includes intrapelvic plates as well as sacroiliac percutaneous screw fixation. Combined includes posterior plating and sacroiliac screw and external fixator anteriorly. All patients showed good results in terms of stability, union of fracture, relief of pain and movements. Two patients had some residual neurological deficit as foot drop. Pelvic ring injuries need a specialized approach for management and outcomes. Application of appropriate classification for management plays a significant role in outcomes.